A COMPARISON OF THE USE OF THE PAST TENSES IN GERMAN AND ENGLISH - Ruziyev, Yarash (Журнал иностранных языков и лингвистики, 2021)
The article is devoted to the use of past tense forms in German and English. It contains some important aspects of the research results.